A genomics-based classification of human lung tumors - Seidel, Danila; Muley, Thomas; Hoffmann, Hans; Schnabel, Philipp Albert (Science translational medicine, 2013)
We characterized genome alterations in 1255 clinically annotated lung tumors of all histological subgroups to identify genetically defined and clinically relevant subtypes. More than 55% of all cases had at least one oncogenic genome alteration potentially amenable to specific therapeutic intervention, including several personalized treatment approaches that are already in clinical evaluation. Marked differences in the pattern of genomic alterations existed between and within histological subtypes, thus challenging the original histomorphological diagnosis. Immunohistochemical studies confirmed many of these reassigned subtypes. The reassignment eliminated almost all cases of large cell carcinomas, some of which had therapeutically relevant alterations. Prospective testing of our genomics-based diagnostic algorithm in 5145 lung cancer patients enabled a genome-based diagnosis in 3863 (75%) patients, confirmed the feasibility of rational reassignments of large cell lung cancer, and led to improvement in overall survival in patients with EGFR-mutant or ALK-rearranged cancers. Thus, our findings provide support for broad implementation of genome-based diagnosis of lung cancer.
Gesehen am 13.09.2021
The Clinical Lung Cancer Genome Project (CLCGP) and Network Genomic Medicine (NGM): Danila Seidel, Thomas Muley, Hans Hoffmann, Philipp A. Schnabel [und viele weitere]